Development of Polymer Based Nanocomposites as a Marker of Cadmium in Complex Matrices. (11th January 2015) - Asiri, Abdullah M.; Akhtar, Kalsoom; Seo, Jongchul; Marwani, Hadi M.; Kim, Dowan; Han, Haksoo; Khan, Sher Bahadar
Abstract : Poly(propylene carbonate)/ β -cyclodextrin (PPC-BCD) nanocomposites were developed as effective extractor for a specific extraction and separation of cadmium(II) by use of inductively coupled plasma-optical emission spectrometry. The selectivity of nanocomposites with different wt% of BCD (PPC-BCD 0.5, PPC-BCD 1, PPC-BCD 3, PPC-BCD 5, or PPC-BCD 10) was investigated toward Cd(II). Based on selectivity and pH studies, Cd(II) was the most quantitatively adsorbed on PPC-BCD 5 phase at pH 6, indicating that PPC-BCD 5 was the most selective toward Cd(II) among other nanocomposites. On the basis of adsorption isotherm study, the superior adsorption capacity of PPC-BCD 5 phase for Cd(II) was found to be 149.25 mg·g −1, following the Langmuir adsorption isotherm model. The kinetic of adsorption for Cd(II) has been examined by pseudo-first- and second-order models. The kinetic exploration suggested a pseudo-second-order kinetic model for the adsorption of Cd(II) on the PPC-BCD 5. Additionally, results of thermodynamic investigation demonstrated favorable spontaneous process for the adsorption mechanism of PPC-BCD 5 toward Cd(II).